1997
DOI: 10.1038/sj.bjp.0701281
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibitor potentiation of bradykinin‐induced venoconstriction

Abstract: 1 Angiotensin-converting enzyme (ACE) inhibitors exert their cardiovascular e ects not only by preventing the formation of angiotensin II (AII), but also by promoting the accumulation of bradykinin in or at the vessel wall. In addition, certain ACE inhibitors have been shown to augment the vasodilator response to bradykinin, presumably by an interaction at the level of the B 2 receptor. We have investigated whether this is a speci®c e ect of the ACE inhibitor class of compounds in isolated endothelium-denuded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 31 publications
(43 reference statements)
0
50
0
Order By: Relevance
“…This interpretation is in agreement with binding studies in which it was also found that there were no alterations in B 2 receptor affinity in the presence of ACE inhibitors. 15,18 In only 1 model of transfected Chinese hamster ovary cells expressing the human B 2 receptor and ACE genes was an increase in the density and affinity of BK binding reported in the presence of enalaprilat. 14 This effect was dependent on the presence of ACE, and it occurred only when enalaprilat was applied in concentrations substantially higher than those needed for the inhibition of the enzymatic activity of ACE, 14 a condition that was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This interpretation is in agreement with binding studies in which it was also found that there were no alterations in B 2 receptor affinity in the presence of ACE inhibitors. 15,18 In only 1 model of transfected Chinese hamster ovary cells expressing the human B 2 receptor and ACE genes was an increase in the density and affinity of BK binding reported in the presence of enalaprilat. 14 This effect was dependent on the presence of ACE, and it occurred only when enalaprilat was applied in concentrations substantially higher than those needed for the inhibition of the enzymatic activity of ACE, 14 a condition that was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat heart, the influence of kininase inhibitors on local kinin concentrations has been established in tracer transit studies that demonstrated a marked increase in kinin concentrations during ACE inhibition specifically in an extravascular distribution compartment. 6 Additional observations have been made suggesting that some of the kinin potentiation properties of ACE inhibitors might be related to mechanisms independent of the inhibition of kinin degradation; for example, (1) ACE inhibitors act as kinin mimetics under conditions in which kinin breakdown should be negligible, 10 (2) ACE inhibitors can enhance the effects of degradation-resistant BK analogs, [11][12][13][14] (3) ACE inhibitors show structure-related differences in their kinin potentiation activities, 15 and (4) ACE inhibitors can provoke a kinin-mediated response even when B 2 receptors have been desensitized through kinin pretreatment. 11,13 The last phenomenon is addressed further here as "receptor resensitization."…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…110 For this reason ACEis have diverse effects independent of their BP-lowering effect (Figure 2). Indeed, different ACEis like moexiprilate, ramipirilate, captopril, enalpril and quinaprilate amplified the effects of bradykinin in vessels that lacked measurable ACE activity 154 and also enhanced the effect of an ACE-resistant B 2 -kinin receptor agonist. These findings demonstrate that ACEis selectively potentiate the B 2 -receptor-mediated vascular effects of bradykinin independently of their ACE-inhibiting properties, and this might be related to differences in molecular structure.…”
Section: Looking Beyond Ace Inhibitionmentioning
confidence: 99%
“…These findings demonstrate that ACEis selectively potentiate the B 2 -receptor-mediated vascular effects of bradykinin independently of their ACE-inhibiting properties, and this might be related to differences in molecular structure. 154,155 ACEis also induce cross-talk between the transmembrane protein ACE and the B 2 -kinin receptor, probably by formation of a heterodimer. This protects high-affinity receptors, blocks receptor desensitization and decreases internalization, thereby potentiating BK beyond blocking its hydrolysis.…”
Section: Looking Beyond Ace Inhibitionmentioning
confidence: 99%